Synthesis and characterization of polystyrene sulfonic acid-polyaniline and montmorillonite nanocomposites - Velauthamurty, Kugamoorthy; Akileshan, Vamadevan (International Journal of Advanced Chemistry, 2016)
Numerous polymer ingredients merged montmorillonite (MMT) has received a great deal of attention in the research field of clay-polymer nanocomposites, due to the enhancements in physical properties such as mechanical and thermal properties compared to their parent materials. MMT-polyaniline-polystyrene sulfonic acid nanocomposites containing different amounts of PANI and PSSA were prepared by the interaction of aniline monomer into pristine MMT together with cation intercalated MMT. It is followed by the subsequent oxidative polymerization of the aniline and PSSA in the interlayer spacing to give MMT-PANI-PSSA nanocomposites. X-Ray diffraction and Fourier-transform infrared spectroscopy results confirmed that PANI and PSSA have been inserted within the MMT interlayer. Thermal Gravimetric Analysis (TGA) shows that the improved thermal stability for the intercalated nanocomposites in comparison with the PANI clay nanocomposites. The thermal behavior of MMT-PANI-PSSA nanocomposites is analyzed in a wide range of temperatures. TGA analysis suggests that the PSSA-PANI of ratio 3:2 is thermally stable. Cyclic votlammogams of the PSSA-PANI- Ce(III) -MMT shows characteristic redox behavior of that appear in the Ce(IV)/Ce(III) under identical conditions together with the typical electrochemical behavior of PSSA. These prepared nanocomposites have several advantages over the other PSSA-MMT nanocomposites such as lesser sheet resistance, advanced hardness and improved thermal stability.